Determinants of investment: sexed semen in dairy cattle - McCullock, Katelyn, author; Hoag, Dana, advisor; Seidel, George, committee member; Wailes, William, committee member; Parsons, Jay, committee member (Colorado State University. Libraries, 2010)
The process of sexing semen through flow cytometry has achieved results in several species, including humans. Potentially, the dairy industry has the ability to earn large gains from sexed semen because of the need for all female herds. This research examined key components in the areas of technology, management, and market environment that affect the adoption of sexed semen on a commercial dairy farm. A spreadsheet was built to simulate the interactions among these areas of interest and regression was used to map and simplify the results. Three scenarios were compared on a case farm using sexed semen. Results identify Dairy heifer calf price had the most impact on profitability of this technology. Conception rate and technology variables affecting conception rate also had significant impacts on return on investment.
Keywords: Dairy cattle -- Breeding; Dairy farming; Semen